Analisis Kebutuhan Stakeholder dalam Transformasi Menuju SMTK dan SMAK Negeri Kupang yang Unggul - Roimanson Panjaitan; Adriana Indra Santi Sole; Rita; Difat Saetban (Fakultas Ilmu Keguruan dan Pendidikan, Universitas Kristen Indonesia, 2026)
This study aims to identify the needs and expectations of stakeholders in the process of transforming Christian religious schools into high-quality educational institutions. The primary focus is to map the expectations of students, teachers, parents, and the government in facing the challenges of the disruption era. The research employs a mixed-methods approach, combining qualitative and quantitative data. Data were collected through questionnaires, in-depth interviews, and Focus Group Discussions (FGD) involving stakeholders at SMPTK Tarus and SMAK Kupang. Research instruments also included observation sheets and school report document analysis. The results indicate a strong consensus that the revision of vision, mission, and a curriculum responsive to information technology are urgent needs. Teachers focus on competency enhancement, while parents prioritize infrastructure improvements and more transparent, accountable school management. All stakeholders expressed absolute support (100% agreement) for the transformation process, provided the school actively fulfills all transformation indicators. However, the process faces challenges such as limited funding from foundations, infrastructure accessibility, and lengthy administrative procedures for school nationalization. This study contributes to the development of a transformation model for religious schools specifically within the context of Christian education in East Nusa Tenggara by adopting spiritual values and modern educational quality standards. The success of this transformation relies on a comprehensive approach involving four pillars: revitalizing the vision-mission, sustainable teacher development, digitalizing management and curriculum, and strengthening external partnerships.